Cardiovascular malformations in infants of diabetic mothers. Issue 10 (15th September 2003) - Wren, C; Birrell, G; Hawthorne, G
Abstract : Objective: To compare the prevalence at live birth and the spectrum of cardiovascular malformations in infants born to diabetic mothers with pre-existing diabetes with that in infants of non-diabetic mothers. Design: Prospective study of all live births in the resident population of one health region, with recording of details of the outcome of all pregnancies of women with pre-existing diabetes and of all live born babies with cardiovascular malformations. Results: In the six years 1995–2000 there were 192 618 live births in the study population. Cardiovascular malformations were confirmed in 22 of 609 (3.6%) babies with diabetic mothers and in 1417 of 192 009 (0.74%) babies with non-diabetic mothers. The odds ratio for a cardiovascular malformation with maternal diabetes was 5.0 (95% confidence interval 3.3 to 7.8). Combination of these results with previous reports and comparison with the spectrum of cardiovascular malformations in infants of non-diabetic mothers shows a greater than threefold excess of transposition of the great arteries, truncus arteriosus, and tricuspid atresia. Conclusions: Pre-existing maternal diabetes is associated with a fivefold increase in risk of cardiovascular malformations. Transposition of the great arteries, truncus arteriosus, and tricuspid atresia are overrepresented to produce a substantial excess of these malformations.